Innate - Ng, Dan Wei Hao (2019)
What is one thing that you were born with and cannot change but is judged by others?Innate explores an ethnography of discrimination and addresses some of the stereotypes around the world. Every human is born with a set of tangible and intangible characteristics. Yet, these innate traits are constantly being discriminated. People are often judged for things that they cannot change. There is a growing trend of discriminatory comments across different issues and types of people. Many accusations made by netizens are baseless, unsound, and stereotypical. The same word such as black can possess the power of both identity and derogatory nuances. Individuals have the power to amplify their voices to counter hate and promote tolerance. It is important to raise awareness of social issues around the world so that more people can listen, share, and build a healthy community through stories, promoting awareness, tolerance, and empathy. Both explicit and implicit biases can be hard to eradicate but every small step forward is progress.